MICROCONTROLLER BASED WASTE SEGREGATOR AND MANAGEMENT OF WET WASTE TO PRODUCE ORGANIC FERTILIZER - N, NANDINI; N, CHAITRA; R, SUSHMA; M.C, PRUTHVI; H, SACHIN (The journal of contemporary issues in business and government, 2021)
Industrialization, modernization, rapid advancements and increase in population have led to large generation of waste. It is possible to reuse and recycle the waste effectively by segregation. This paper, proposes an prototype model forwaste separator, which is used to separate the dumped waste spontaneously, leads to the production of fertilizer from food waste recycling. The smart-bin is programmed to give the information aboutandumped waste, so that the respective action would be-taken. Many motors& sensors both are interfaced with the Arduino-board in the system [5]. The smart-bin is divided into 3 sections. Everysection has itsrespective function and waste is segregated into dry, metaland wet waste. The research aims to produce organic fertilizer through providing the suitable environment to decompose the wet waste in to Organic Fertilizer.